Apigenin remodels the gut microbiota to ameliorate ulcerative colitis - Fu, Rongrong; Wang, Lechen; Meng, Ying; Xue, Wenqing; Liang, Jingjie; Peng, Zimu; Meng, Jing; Zhang, Min (Frontiers in Nutrition, 2022)
Ulcerative colitis (UC), as a chronic non-specific colorectal inflammatory disease with unclear etiology, has long plagued human health. Gut microbiota dysbiosis destroy homeostasis of the colon, which is closely related to ulcerative colitis progress. Apigenin, a flavonoid widely present in celery, has been found to improve ulcerative colitis. However, the potential molecular mechanism of apigenin ameliorating ulcerative colitis through protecting intestinal barrier and regulating gut microbiota remains undefined. In this study, we evaluated the anti-inflammatory effects and regulation of gut microbiota of apigenin in a mouse model of dextran sodium sulfate (DSS)-induced colitis. The results indicated that apigenin significantly relieved the intestinal pathological injury, increased goblet cells quantity and mucin secretion, promoted anti-inflammatory cytokines IL-10 expression, and inhibited pro-inflammatory cytokines TNF-α, IL-1β, IL-6 and MPO activity of colon tissue. Apigenin obviously increased ZO-1, claudin-1 and occludin expression to restore the intestinal barrier integrity. Moreover, apigenin remodeled the disordered gut microbiota by regulating the abundance of Akkermansia, Turicibacter, Klebsiella, Romboutsia, etc and its metabolites SCFAs, attenuating DSS-induced colon injury. We also investigated the effect of apigenin supplementation on potential metabolic pathways of gut microbiota. In conclusion, with low toxicity and high efficiency, apigenin might serve as a potential therapy strategy for the treatment of UC via regulating the interaction and mechanism between host and microorganism.